Radiation therapy induces immunosenescence mediated by p90RSK - Imanishi, Masaki; Cheng, Haizi; Kotla, Sivareddy; Deswal, Anita; Le, Nhat-Tu; Chini, Eduardo; Ko, Kyung Ae; Samanthapudi, Venkata S. K.; Lee, Ling-Ling; Herrmann, Joerg; Xu, Xiaolei; Reyes-Gibby, Cielito; et al. (Frontiers in Cardiovascular Medicine, 2022)
Radiation therapy (RT) to the chest increases the patients’ risk of cardiovascular disease (CVD). A complete understanding of the mechanisms by which RT induces CVD could lead to specific preventive, therapeutic approaches. It is becoming evident that both genotoxic chemotherapy agents and radiation induce mitochondrial dysfunction and cellular senescence. Notably, one of the common phenotypes observed in cancer survivors is accelerated senescence, and immunosenescence is closely related to both cancer risk and CVD development. Therefore, suppression of immunosenescence can be an ideal target to prevent cancer treatment-induced CVD. However, the mechanism(s) by which cancer treatments induce immunosenescence are incompletely characterized. We isolated peripheral blood mononuclear cells (PBMCs) before and three months after radiation therapy (RT) from 16 thoracic cancer patients. We characterized human immune cell lineages and markers of senescence, DNA damage response, efferocytosis, and determinants of clonal hematopoiesis of indeterminant potential (CHIP), using mass cytometry (CyTOF). We found that the frequency of the B cell subtype was decreased after RT. Unsupervised clustering of the CyTOF data identified 138 functional subsets of PBMCs. Compared with baseline, RT increased TBX21 (T-bet) expression in the largest B cell subset of Ki67-/DNMT3a+naïve B cells, and T-bet expression was correlated with phosphorylation of p90RSK expression. CD38 expression was also increased in naïve B cells (CD27-) and CD8+ effector memory CD45RA T cells (TEMRA). In vitro, we found that p90RSK activation by ionizing radiation (IR) was critical in upregulating immunosenescence-associated CD38+/T-bet+ memory, naïve B, and myeloid cells, suggesting the crucial role of p90RSK activation in immunosenescence. The critical role of p90RSK activation in immune cells and T-bet induction in upregulating atherosclerosis formation has been reported. Furthermore, T-bet directly binds to the CD38 promoter region and upregulates CD38 expression. Since both T-bet and CD38 play a significant role in the process of immunosenescence, our data provide a cellular and molecular mechanism that links RT-induced p90RSK activation and the immunosenescence with T-bet and CD38 induction observed in thoracic cancer patients treated by RT and suggests that targeting the p90RSK/T-bet/CD38 pathway could play a role in preventing the radiation-associated cardiovascular disease and improving cancer prognosis by inhibiting immunosenescence.